POUR UNE GOUVERNANCE REPENSEE - Ivara, Gilbert (IJRDO - Journal of Social Science and Humanities Research, 2022)
In many countries of the South, the management of public affairs suffers because of a persistent mismatch between the spirit of governance and its implementation in terms of praxis. Some think, rightly, that this deficit must be justified by a difficult compatibility between the spirit of governance and the weight of traditions. This article sets out to identify in the African imagination ways of thinking and acting as possible seeds of resistance to the notion of governance, a paradigm of neoliberal inspiration.